2018
DOI: 10.1177/0033294118806473
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thinking Dispositions, General Ability, Numeracy, and Instructional Set on Judgments and Decision-Making

Abstract: To explore hypotheses based on Stanovich’s proposal that analytic processing comprises a reflective-level, an algorithmic level, and specific mindware, 342 participants completed measures of thinking dispositions, general ability (GA), numeracy, and probabilistic and nonprobabilistic reasoning. In a control condition, numeracy predicted probabilistic reasoning at high levels of both thinking dispositions and GA, and GA predicted nonprobabilistic reasoning at high levels of thinking dispositions. In a logic ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…It is troublesome that education and attention to news did not predict attitudes and behaviors as much as ideology: People with more information and greater skill to use it should have greater understanding and make more normative choices, consistent with public health guidelines. In fact, for most non-COVID-19-related issues, greater intelligence and specific cognitive abilities (e.g., knowledge, numeracy, literacy) are associated with more accurate decisions (e.g., Bruine de Bruin, Parker, & Fischhoff, 2007 ; De keersmaecker & Roets, 2017 ; Klaczynski & Felmban, 2020 ; Murphy & Hall, 2011 ; Peters et al, 2006 ; Stanovich & West, 2008 ), taking more protective health behaviors (e.g., Dieckmann et al, 2015 ), and better health outcomes (e.g., Cavanaugh et al, 2008 ; Estrada, Martin-Hryniewicz, Peek, Collins, & Byrd, 2004 ; Gottfredson & Deary, 2004 ; Peters et al, 2017 ). Cognitive ability should help people evaluate evidence in more normative fashion and come to accurate conclusions about how to respond to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…It is troublesome that education and attention to news did not predict attitudes and behaviors as much as ideology: People with more information and greater skill to use it should have greater understanding and make more normative choices, consistent with public health guidelines. In fact, for most non-COVID-19-related issues, greater intelligence and specific cognitive abilities (e.g., knowledge, numeracy, literacy) are associated with more accurate decisions (e.g., Bruine de Bruin, Parker, & Fischhoff, 2007 ; De keersmaecker & Roets, 2017 ; Klaczynski & Felmban, 2020 ; Murphy & Hall, 2011 ; Peters et al, 2006 ; Stanovich & West, 2008 ), taking more protective health behaviors (e.g., Dieckmann et al, 2015 ), and better health outcomes (e.g., Cavanaugh et al, 2008 ; Estrada, Martin-Hryniewicz, Peek, Collins, & Byrd, 2004 ; Gottfredson & Deary, 2004 ; Peters et al, 2017 ). Cognitive ability should help people evaluate evidence in more normative fashion and come to accurate conclusions about how to respond to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, as suggested above in our discussion about confidence, the implementation of the domain-specific competence of numeracy would depend to some extent on metacognitive thinking dispositions 21 , 23 , 63 . Researchers tested this hypothesis, distinguishing general ability (fluid intelligence), numeracy and thinking disposition (reflective versus impulsive) to study their relationships to probabilistic reasoning (an example of numerical processing) 64 . They found that, although individual differences in thinking disposition (metacognition) did not moderate the relation between numeracy and probabilistic reasoning, an experimentally induced thinking ‘disposition’ did moderate it.…”
Section: Defining and Measuring Numeracymentioning
confidence: 99%
“…In addition, although the CRT and numeracy tests correlated with one another, the CRT also accounted for unique variance beyond numeracy in predicting risk and ratio judgements 33 , 45 (see also refs. 59 , 64 ). In a study in which subjects described their thinking aloud, it was similarly concluded that the CRT is a multi-faceted construct rather than a single dimension, as both numeracy and reflectivity accounted for performance 71 .…”
Section: Defining and Measuring Numeracymentioning
confidence: 99%
See 1 more Smart Citation